2002
DOI: 10.1089/105072502760258613
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for a Strong Genetic Influence on the Development of Autoimmune Thyroid Disease: The California Twin Study

Abstract: To determine the heritable component of Graves' disease (GD) more precisely, a disease survey questionnaire completed by 13,726 California-born twin pairs over the age of 37 years was used as the foundation of this study. On the basis of this survey, each member of pairs reporting a past diagnosis of GD was then sought for an extensive telephone interview to seek diagnostic confirmation. Successful diagnostic evaluation occurred in 108 cases, of which 99 affected twin pairs form the basis of this report. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 40 publications
1
37
1
1
Order By: Relevance
“…Environmental factors play also an important role in the development of AITD, as the concordance rate for AITD in monozygotic twins is not 100% (27,28). Twin studies suggest that genetic factors account for about 70% of the risk of developing AITD leaving about 30% for the environmental factors (27)(28)(29)(30). Identified environmental factors are iodine intake, smoking, stress, pregnancy, estrogens, and possibly infections.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors play also an important role in the development of AITD, as the concordance rate for AITD in monozygotic twins is not 100% (27,28). Twin studies suggest that genetic factors account for about 70% of the risk of developing AITD leaving about 30% for the environmental factors (27)(28)(29)(30). Identified environmental factors are iodine intake, smoking, stress, pregnancy, estrogens, and possibly infections.…”
Section: Discussionmentioning
confidence: 99%
“…AITDs are complex diseases, which are caused by an interaction between susceptibility genes (6)(7)(8) and nongenetic factors, such as infection (9)(10)(11)(12). This paradigm is based on solid epidemiologic evidence demonstrating a genetic predisposition to AITDs, including: (i) familial clustering (13); (ii) a sibling risk ratio ( s ) of Ͼ10 (7,14); (iii) a high concordance rate in monozygotic twins when compared with dizygotic twins (15)(16)(17)(18); and (iv) the presence of thyroid autoantibodies, which are markers of subclinical AITD, in up to 50% of siblings of patients with AITD (19,20).…”
mentioning
confidence: 99%
“…Studies with twins have indicated a higher concordance of autoimmune disorders in monozygotic twins compared to dizygotic twins [31][32][33]. In addition to these findings in humans, certain inbred murine strains show a consistent susceptibility to particular spontaneous or experimentally induced autoimmune diseases [34,35].…”
Section: Genetic Basis Of Autoimmunitymentioning
confidence: 95%